On Lotka-Volterra evolution law - Mukhamedov, Farrukh; Saburov, Mansoor (Hikari Ltd, 2011)
In this paper we study a Lotka-Volterra (LV) evolution law. We give a mathematical model of the LV evolution law. This model includes into itself the classical LV predator-prey model as a particular case. One of the basic results is that under suitable conditions the classical LV predator-prey model can exhibit any asymptotical behavior such as equilibrium states, periodic cycles, and attractors. In this paper we provide some LV type models in which one can observe any asymptotical behavior such as equilibrium states, periodic cycles, and attractors.